A biblical approach to the reduction of child poverty in Anambra state, Nigeria - Echeta, Uzonna F. (HTS teologiese studies, 2020)
Child poverty reduction is one of the most important and urgent tasks that requires attention in most regions of the world, nations and Anambra state specifically. The population of impoverished children is progressively increasing in Nigeria because of economic recession and poor security situations that lead to displacement and death of their parents. Although children constitute half of the entire population, commensurate attention is not given to them to match the dimensions of poverty they face. This study argued that child poverty is multidimensional, evidenced in lack of safe drinking water, adequate nutrition, shelter, decent sanitation, medical advice or health services (immunisations) and education, to mention a few. The article highlighted the laudable efforts of the United Nations International Children’s Emergency Fund (UNICEF) and Anambra government and maintained that multiple strategies can help in solving this problem. To complement these efforts, the enforcement of biblical policies or principles about children’s rights would in no small measure reduce child poverty. It was concluded that a proper repositioning of children would be matched with implementation of biblical strategies. Biblical intervention could help children socially, mentally and psychologically and in their general well-being. Biblical principles would erase wrong socio-cultural notions about children.